THE EXORDIUM OF MARCION'S ANTITHESES - Burkitt, F. C. (The journal of theological studies, 1929)
F. C. BURKITT; THE EXORDIUM OF MARCION'S ANTITHESES, The Journal of Theological Studies, Volume os-XXX, Issue April, 1 April 1929, Pages 279–280, https://doi.or